(untitled) (Applied Biological Research, 2023)
The study aims to investigate the mucoadhesive properties of neem fruit mucilagebyincorporatingitintomucoadhesive microspheres with Acyclovir (ACR) as a model drug. Nine interpretations of mucoadhesive microspheres were made with carbomer-934P and varying proportions of neem fruit mucilage (NFM). A central composite design with Design Expert software to check the impact of independent variables (neem mucilage and carbomer 934P levels) on entrapment efficacy and mucoadhesion time. As part of congeniality studies, the microspheres were examined for ACR content and liberation. The study revealed that ACR entrapment increased with increase in NFM levels in the formulations and that the mucoadhesion time was greater in formulations with higher NFM levels. In the formulations containing higher levels of NFM, the drug release was slightly reduced. Acyclovir is capable of good stomach-specific drug delivery by carbomer 934P and its delivery is enhanced by neem fruit mucilage when prepared as mucoadhesive microspheres.